2015
DOI: 10.1021/acsami.5b01592
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Stimuli-Responsive Microparticles

Abstract: The need for smart materials in the area of biotechnology has fueled the development of numerous stimuli-responsive polymers. Many of these polymers are responsive to pH, light, temperature, or oxidative stress, and yet very few are responsive toward multiple stimuli. Here we report on the synthesis of a novel dual-stimuli-responsive poly(ethylene glycol)-based polymer capable of changing its hydrophilic properties upon treatment with UV light (exogenous stimulus) and markers of oxidative stress (endogenous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 44 publications
0
54
0
Order By: Relevance
“…21 In the past decade, the fabrication of multicompartmental fibers and particles with two to seven different compartments and with various shapes via EHD co-jetting has been well-established. [22][23][24][25][26] Additionally, within these systems, the incorporation of water-based and organicbased polymers, 25,[27][28][29] functional polymers for the creation of specific targeting and stealth patches on the surface of the particles, 30,31 stimuliresponsive polymers for on-demand therapeutic release kinetics, [32][33][34] small molecule-based therapeutics, [33][34][35] DNA-based therapeutics, 36 protein-based therapeutics, 35 and imaging agents 22 have been explored. Furthermore, the interaction of such systems with various cell types, 34,[36][37][38][39][40][41] their biodistribution in vivo, 42 and their functionality as carriers for dual therapeutic delivery to the cochlea 35,43 have demonstrated that multifunctional systems fabricated based on EHD co-jetting can be ideal carriers for targeted delivery in various applications.…”
mentioning
confidence: 99%
“…21 In the past decade, the fabrication of multicompartmental fibers and particles with two to seven different compartments and with various shapes via EHD co-jetting has been well-established. [22][23][24][25][26] Additionally, within these systems, the incorporation of water-based and organicbased polymers, 25,[27][28][29] functional polymers for the creation of specific targeting and stealth patches on the surface of the particles, 30,31 stimuliresponsive polymers for on-demand therapeutic release kinetics, [32][33][34] small molecule-based therapeutics, [33][34][35] DNA-based therapeutics, 36 protein-based therapeutics, 35 and imaging agents 22 have been explored. Furthermore, the interaction of such systems with various cell types, 34,[36][37][38][39][40][41] their biodistribution in vivo, 42 and their functionality as carriers for dual therapeutic delivery to the cochlea 35,43 have demonstrated that multifunctional systems fabricated based on EHD co-jetting can be ideal carriers for targeted delivery in various applications.…”
mentioning
confidence: 99%
“…(Bahadur, Thapa, & Xu, ; B. Cheng et al, ; Cong et al, ; Y. Gao & Dong, ; F. Wu et al, ; Z. Xu, Liu, Kang, & Wang, ). This “intelligent” nanomedicine possesses the properties of programmed site‐specific drug release behavior for improved cancer treatment (R. Cheng, Meng, Deng, Klok, & Zhong, ; Kakwere et al, ; Sokolovskaya, Rahmani, Misra, Brase, & Lahann, ; F. Xu et al, ). The named DOX/Au@Pt‐cRGD nanocarrier showed controlled drug release behavior, which dual trigged by pH and NIR laser (Q. Yang et al, ).…”
Section: Dual and Multi‐responsive Nanomedicinementioning
confidence: 99%
“…More recently, the development of electrohydrodynamic (EHD) cojetting, which imparts multiple chemical functionalities within distinct compartmental domains of both particles and fibers, has shown great promise in creating more complex drug delivery platforms as well as patterned targeting domains . Additionally, multicomponent fibers have shown promise in creating next‐generation tissue engineering constructs and stimuli‐responsive micro‐ and nanoactuators .…”
Section: Introductionmentioning
confidence: 99%
“…[6] This technology has been implemented in a variety of applications ranging from chemical sensors, [7,8] filtration membranes, [9,10] and tissue engineering, [10][11][12][13] to drug delivery vehicles [5,14] and microencapsulation. [15] More recently, the development of electrohydrodynamic (EHD) cojetting, [16] which imparts multiple chemical functionalities within distinct compartmental domains of both particles and fibers, has shown great promise in creating more complex drug delivery platforms [17][18][19] as well as patterned targeting domains. [20,21] Additionally, Electrohydrodynamic cojetting can result in fibers (electrospinning) and particles (electrospraying) with complex, bicompartmental architectures.…”
mentioning
confidence: 99%